THE DEVELOPMENT OF AFRICAN AMERICAN LITERARY TRADITION: VOICE, IDENTITY, AND RESISTANCE IN AMERICAN LITERATURE - Iroda Egamberdiyeva Abdurahimovna; Qodirov Izzatillo Xayrullo o‘g‘li (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the development of the African American literary tradition in American literature, focusing on themes of voice, identity, and resistance. The study explores how African American writers have used literature as a powerful tool to express cultural identity, challenge racial oppression, and articulate social injustice. The research highlights key literary figures such as Langston Hughes, Zora Neale Hurston, and Toni Morrison, whose works reflect the evolution of African American cultural expression across different historical periods. Their writings address issues of slavery, segregation, identity formation, and cultural memory. Furthermore, the article argues that African American literature has played a crucial role in shaping American literary identity by introducing diverse perspectives and challenging dominant cultural narratives. The study also emphasizes the importance of literary resistance as a means of empowerment and social transformation.